Poverty reduction strategy and monitoring system in Region IX an exploratory analysis - Campiseño, Evelyn R.; Maratas, Ed Neil O. (2016)
Poverty is one of the challenges facing the country for several decades. This study aims to explore the poverty reduction strategy and monitoring existing in the Zamboanga peninsula. It utilized data on poverty incidence of Zamboanga Peninsula from 2006 – 2012. The findings revealed that Zamboanga del Norte was still in on the top 10 poorest provinces in the Philippines as of 2013. There was a slow decline in the number of poor families in Zamboanga Peninsula from 2006 – 2012. Meanwhile, international organizations took a vital role in the development of poverty reduction program in the Philippines. Despite the many interventions, the implementation of poverty reduction program with specific administration seems to be coterminous. It has a short life span thus resulting to low impact on reducing the number of poor families specifically, in Zamboanga Peninsula. Thus, a massive and thorough monitoring of various poverty reduction strategies conducted to check if the target beneficiaries really benefited the program. In addition, studies related to poverty reduction strategies and poverty monitoring in Zamboanga Peninsula will be conducted through direct or interview method.
Keywords: Mindanao studies; Poverty reduction; Poverty